2003
DOI: 10.1200/jco.2003.01.101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish Oil on Appetite and Other Symptoms in Patients With Advanced Cancer and Anorexia/Cachexia: A Double-Blind, Placebo-Controlled Study

Abstract: Fish oil did not significantly influence appetite, tiredness, nausea, well-being, caloric intake, nutritional status, or function after 2 weeks compared with placebo in patients with advanced cancer and loss of both weight and appetite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1
13

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(106 citation statements)
references
References 27 publications
4
88
1
13
Order By: Relevance
“…Of parenthetical note, this drop-out rate during the first month is typical of studies in patients with cancer-associated anorexia and weight loss, a syndrome that carries a poor prognosis [10,11,18,19]. Baseline characteristics are illustrated in Table 1 and are notable for 58% of patients (n=69) reporting a weight loss of more than 10 pounds in the preceding 2 months.…”
Section: Resultsmentioning
confidence: 90%
“…Of parenthetical note, this drop-out rate during the first month is typical of studies in patients with cancer-associated anorexia and weight loss, a syndrome that carries a poor prognosis [10,11,18,19]. Baseline characteristics are illustrated in Table 1 and are notable for 58% of patients (n=69) reporting a weight loss of more than 10 pounds in the preceding 2 months.…”
Section: Resultsmentioning
confidence: 90%
“…This high drop-out rate compromised our ability to assess long-term toxicity of continued treatment with this combination and did not allow us to obtain complete pharmacokinetic data on all patients. Although this drop-out rate might be considered a limitation of this study, it is typical of what is observed in cancer-associated weight loss trials and in non-small-cell lung cancer trials [18,19,20] and is, thus, in effect, unavoidable.…”
Section: Discussionmentioning
confidence: 90%
“…While smaller trials resulted in significant weight gain in 20 cachectic pancreatic cancer patients after 3 to 7 weeks of fish oil-enriched dietary supplementation as shown by Barber et al [18] and improved survival rate in 60 tumor patients after dietary supplementation of fish oil as shown by Gogos et al [19], the outcomes of major comparative studies do not clearly support these positive results. Bruera et al [20] investigated fish oil versus placebo in 60 patients with advanced tumor disease and weight loss and found no significant effect on weight loss or appetite. It must be taken into consideration that appetite was the primary endpoint, not weight loss, and duration of the trial with a 2-week intervention period was very short.…”
Section: Introductionmentioning
confidence: 98%
“…As evaluated by Burns et al in their phase I and II clinical trials with marine fatty acid ethyl ester softgel formulation, relatively high dosage (7.5 g/day EPA plus DHA) was needed to positively affect tumor-associated weight loss, causing marked compliance problems like gastrointestinal side effects and belching with fishy taste or smell [23,24]. Even lower dose of 1.2 g/day EPA plus 1.2 g/day DHA, supplied as fish oil capsules in the study by Bruera et al [20] caused significant compliance problems. As critically reviewed by Jatoi [25], the devastating nature of the cancer anorexia/weight loss syndrome and the still persisting lack of its successful clinical management merits further studies and novel approaches to n−3 fatty acid supplementation in cancer cachexia.…”
Section: Introductionmentioning
confidence: 99%